Validity of Clinical Diagnostic Signs in the Examination of Individuals Suspected of Temporomandibular Disorders Using the Hamburg Protocol - Shybinska, М. В.; Makeyev, В. Ф. (Actual Dentistry, 2025)
Purpose. To determine the validity of clinical diagnostic signs in the examination of individuals suspected of temporomandibular disorders using the Hamburg Protocol. Materials and Methods. The study included 60 patients with temporomandibular disorders (TMD) aged 20–69 years, among whom 80% were women, and 63% were individuals aged 30–49 years. Diagnosis encompassed general dental examination, the Hamburg Protocol, panoramic radiography, CT, MRI (as indicated), and axiography. Patients were stratified into groups with muscular, articular, and combined disorders. Results. It was found that 51.67% of patients had muscular disorders, 16.67% had articular disorders, and 31.67% had combined disorders. Among patients with muscular disorders, 77.4% exhibited only two symptoms, whereas in combined disorders, symptoms were more numerous (36.8% had three, 31.6% had four, and 26.3% had five). The most frequent symptoms were pain on palpation of the masticatory muscles (100% in muscular disorders, 94.7% in combined disorders) and the presence of joint noises and impaired opening trajectory (80% each in particular disorders, 78.9% each in combined disorders). The symptom “premature contacts” was observed in over 50% of patients across all groups. Conclusions. The Hamburg Protocol is considered a suitable diagnostic test for the preliminary rapid diagnosis of temporomandibular disorders, even in cases with only two symptoms.